2019
DOI: 10.1080/20008198.2019.1686801
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adaptation and posttraumatic stress disorder among Syrian refugees in Germany: a mixed-methods study investigating environmental factors

Abstract: Background: Considering the exposure to potentially traumatic events among the growing refugee population worldwide, there is an urgent need to better understand potential risk and protective factors that may be associated with psychological adaptation in Syrian refugees residing in GermanyObjective: The present study examined trauma-related coping self-efficacy, resilience, and environmental factors as predictors of psychological adaptation and posttraumatic stress disorder (PTSD).Method: The present study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 26 publications
5
37
1
Order By: Relevance
“…Highly efficacious patients are more likely to perceive obstacles as challenges to be mastered, in turn lowering stress and reducing susceptibility to depression (32). A recent study found an association between a higher perceived ability to handle traumatic events and improved psychological adaptation among Syrian refugees (33). We did not find any statistically significant association between low perceived social support, an established contributor to mental health issues (34), and higher levels of depression.…”
Section: Discussioncontrasting
confidence: 90%
“…Highly efficacious patients are more likely to perceive obstacles as challenges to be mastered, in turn lowering stress and reducing susceptibility to depression (32). A recent study found an association between a higher perceived ability to handle traumatic events and improved psychological adaptation among Syrian refugees (33). We did not find any statistically significant association between low perceived social support, an established contributor to mental health issues (34), and higher levels of depression.…”
Section: Discussioncontrasting
confidence: 90%
“…Most studies included different ethnic groups such as Syrian, Afghan, Iraqi and others, and ethnic groups varied among studies. Four studies focused on Syrian refugees (52,53,61,62), however, in all other studies the majority of ASRs were also Syrian. In all studies reporting gender distribution, the proportion of men was higher (60.3 to 85.1%), with the exception of one study with 60.0% female participants (60).…”
Section: Descriptive Data Of Included Studiesmentioning
confidence: 99%
“…Seventeen different instruments were used in these studies. In six studies, questionnaires were completed by participants (self-report) (50,52,53,55,61,62), while the studies by Comtesse and Rosner (54) and Kaltenbach et al (60) used semi-structured clinical interviews, and five studies conducted computer-assisted face-to-face interviews (51,(56)(57)(58)(59). All instruments used in the studies and their validity are presented in Supplementary Table A3.…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 99%
“…A longitudinal follow-up study is warranted. This is because while there appears to be a high prevalence of mental health problems in the initial resettlement period among Syrian refugees (El Arnaout et al, 2019), over the longer-term prevalence of mental health symptoms is determined by the degree of trauma exposure and post-migration stress (Bogic, Njoku, & Priebe, 2015;von Haumeder, Ghafoori, & Retailleau, 2019). This study specifically aimed to (1) investigate the levels of post-migration stress, mental health (PTSD, anxiety, depression), and sleep symptoms in Syrian refugees at 12-month follow-up; (2) investigate which Time 1 variables predicted mental health symptoms at 12-month followup (Time 2); and (3) conduct exploratory analyses examining whether our cross-sectional findings (i.e.…”
Section: 叙利亚难民中创伤暴露 移民后压力 睡眠障碍和心理健康之间的关系的 纵向调查mentioning
confidence: 99%